Ocular complications in heart, lung and heart-lung recipients. Issue 3 (11th October 2006) - Akerele, Toks; Lightman, Susan
Abstract : Aim: To prospectively assess ocular morbidity and the need for ocular screening in patients on long term, high dose immunosuppression for the maintenance of solid organ transplants. Methods: Dilated ocular examinations were performed on patients receiving immunosuppression for the maintenance of heart, lung and heart-lung transplants. Patients were examined repeatedly in the post transplant period. Results: Of the 115 transplant recipients examined 62 (54%) had ocular findings. The most common findings were cataracts (17% of those examined) followed by hypertensive change (8%), chorioretinal scarring (5%) and diabetic retinopathy (3%). One patient developed ocular infective complications following surgery due to Aspergillus spp . endophthalmitis. 18 patients (16%) were symptomatic at examination with the most common symptom being blurred vision. The most common finding in symptomatic patients was cataract with almost a quarter of patients having posterior subcapsular lens opacity that could be attributed to steroid therapy. Conclusion: Patients had surprising low incidences of ocular infective complications despite previous reports. It is likely that this is due to improved immunosuppression regimes and improved monitoring of immunosuppression in the early post-transplant period. The screening of asymptomatic individuals following heart, lung or heart-lung transplantation was not supported by this study.